Organotypic Brain Slice Cultures. (12th October 2018) - Humpel, Christian
Abstract: Ex vivo cell culture models are of particular interest for neurobiologists, as these allow the study of brain cells in an isolated environment. Organotypic brain slice cultures allow growth of three‐dimensional brain tissue that conserves the cellular architecture. This unit describes the preparation and culturing of organotypic brain slices from mice. In three basic protocols, the general procedure, the specific preparation of chopper slices, and slicing of whole‐brain vibratome sections are described. Support protocols explain the use of postnatal or adult mice, the preparation of coronal or sagittal slices, the preparation of co‐cultures, post‐processing of slices, the use of extra filter membranes, and the re‐use of membrane inserts. This unit provides an easy‐to‐understand methodological introduction to brain slice cultures. © 2018 by John Wiley & Sons, Inc.